A Comparison of Four Molecular Methods for Detection of Aflatoxin-Producing Aspergillus in Peanut and Dried Shrimp Samples Collected from Local Markets around Pathum Thani Province, Thailand. (24th December 2020) - Kumsiri, Ratchanok; Kanchanaphum, Panan
Abstract : Aspergillus flavus is an aflatoxin-producing fungus which is poisonous to humans and animals when consumed. Detecting the fungus can help to prevent this danger. The four molecular methods, namely, conventional isothermal amplification (LAMP), PCR, quantitative LAMP (qLAMP), and qPCR, were compared to determine their efficiency for A. flavus detection. Thirty samples of peanut and dried shrimp were collected from 15 markets around Pathum Thani Province in Thailand. The samples were artificially infected with 10 8 conidia/ml of A. flavus for 1 hr and enriched for one day to represent real contamination. The results show that the sensitivity detection for A. flavus in PCR, LAMP, qPCR, and qLAMP was 50 ng, 5 ng, 5 pg, and 5 pg, respectively. Aspergillus in 30 peanut and dried shrimp from the market was detected by all four methods. The detection rate was about 20%, 60%, 100%, and 100% with PCR, LAMP, qPCR, and qLAMP, respectively. The molecular detection technique, especially LAMP, qPCR, and qLAMP, can detect this pathogenic fungi very rapidly with high sensitivity and reliability in comparison to conventional PCR.